Parental Relationship with Twins from Pregnancy to 3 Months: The Relation Among Parenting Stress, Infant Temperament, and Well-Being - Prino, Laura E.; Rollè, Luca; Sechi, Cristina; Patteri, Luciana; Ambrosoli, Anna; Caldarera, Angela M.; Gerino, Eva; Brustia, Piera (Frontiers in Psychology, 2016)
Objective: The transition to parenthood, from pregnancy to postpartum period, is a critical process, particularly for couples expecting twins. There is very little literature regarding the links between anxiety, depression, dyadic adjustment, parental stress, and infant temperament spanning from pregnancy to postpartum. This study has two aims: first, to examine whether mothers’ and fathers’ anxiety, depression, and dyadic adjustment, assessed at the sixth month of pregnancy and three months postpartum, are associated with infants' negative affectivity and parenting stress; second, to examine whether there is any difference between fathers’ and mothers’ levels of parenting stress and perception of the twins’ temperament, as well as to evaluate, separately for mothers and fathers, whether the levels of parenting stress and perception of child temperament differ for each twin. Method: The study participants were 58 parents (29 couples) and their healthy 58 twin babies (51.7% boys, 48.3% girls). Mothers’ ages ranged from 30 to 44 years, (MAge = 36.3 years, SD = 3.2 years), and fathers’ ages ranged from 32 to 52 years, (MAge = 38.2 years, SD = 4.4 years). The parents, during the pregnancy period and three months after delivery, filled out the Edinburgh Postnatal Depression Scale, the State-Trait Anxiety Inventory, and the Dyadic Adjustment Scale. Three months after delivery they also filled out the Parenting Stress Index—Short Form and the Infant Behavior Questionnaire Revised. Results: The analyses showed a significant correlation between parental anxiety/depression symptoms and infants’ negative affectivity and parenting stress (in both mothers and fathers). Moreover, compared to fathers, mothers reported higher scores on specific dimensions of the infants’ negative affectivity, (t (28) = -2.62 and p < .05; t (28) = 2.09 and p < .05), and parenting stress, (t (28) = 2.19 and p < .05; t (28) = 2.23 and p < .05), but only for Twin 2. Finally, the results showed that mothers' perceptions of child temperament vary between two twins, (e.g., distress to limitations: t(28) = 2.08 and p <.05). Discussion: This study highlights the peculiarity of twin parenthood during the fourth trimester. In particular, the differences between twins’ mothers’ and fathers’ perceptions.